Crafting collaborative research methodologies : leaps and bounds in interdisciplinary inquiry - Pedersen, Christina Hee (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book demonstrates a number of collaborative, visual and narrative methods that explore the promises and the ethical, relational complexities inherent in collaborative research. The book brings together the fruits of many years of work with interdisciplinary, collaborative research methodologies, showing the challenges and rewards inherent in the practice of real collaborative research. It represents a condensation and a reflexive exploration of knowledge (co)produced through innovation and experimentation in both research and teaching over more than three decades of the author's experience. Suitable for all students of qualitative and collaborative methodology"--
Speaking an Opening Text: About Thinking Positions -- A Conceptual Repertoire for Analysis: Crosscutting Concepts -- "The Image Exercise": A Collaborative Method to Explore Relations and Meanings -- Putting the Image Exercise to Work: On Gender and Humour -- To Take on Memory Work: Surrendering to Collaboration and Process -- Longing for Feminist Activism: The Doings in Memory Work -- A Body in a Text: Exploring the Productivity of Difference -- Attending to the Tensions: Putting Intersectional Thinking to Work -- Taking in and Speaking Out Social Differentiation: Moving Evocation and Interpretation -- Pushing the Boundaries: Ideas to Generate Texts for Analysis -- Opening a Closure -- The Tensions, Leaps and Stumbles: A Dialogue on Research and Activism / Bolette Frydendahl Larsen, Christina Hee Pedersen and Louise Phillips.
OCLC-licensed vendor bibliographic record.
Keywords: Interdisciplinary research -- Methodology; Action research -- Methodology; Qualitative research -- Methodology; Intersectionality (Sociology); PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Research